Draft Genome Sequence of Burkholderia puraquae Type Strain CAMPA 1040, Isolated from Hospital Settings in Córdoba, Argentina - Leguizamón, Mariana (2017)
We report here the draft genome sequence of Burkholderia puraquae type strain CAMPA 1040, a member of the Burkholderia cepacia complex. This strain, isolated from a hemodialysis water reservoir, harbors several stress tolerance genes, such as the systems for low oxygen survival, for copper tolerance, and for osmotic stress resistance.